Arminianism, Catholicism, and Puritanism in England During The 1630s - Questier, Michael ca. 20./21. Jh. (The historical journal, 2006)
The relationship between Arminianism and Roman Catholicism in the early Stuart period has long been a source of historiographical controversy. Many contemporaries were in no doubt that such an affinity did exist and that it was politically significant. This article will consider how far there was ideological sympathy and even rhetorical collaboration between Caroline Catholics and those members of the Church of England whom both contemporaries and modern scholars have tended to describe as Arminians and Laudians. It will suggest that certain members of the English Catholic community actively tried to use the changes which they claimed to observe in the government of the Church of England in order to establish a rapport with the Caroline regime. In particular they enthused about what they perceived as a strongly anti-puritan trend in royal policy. Some of them argued that a similar style of governance should be exercised by a bishop over Catholics in England. This was something which they believed would correct the factional divisions within their community and align it more effectively with the Stuart dynasty.